O contrabaixo acústico na música popular brasileira: utilização de arranjos como ferramenta para ampliação do repertório e material didático - Ribeiro, Gadiego Cararo (2014)
This paper is the final product of the Master of Music course – Performance of Musical Double Bass, Graduate School of Music of the Federal University of Goiás and is divided into two parts. Part A: artistic production which includes two recitals with program related to the developed research and there are also mandatory for the conclusion of the course, and Part B: an scholar paper. The final recital has works that highlight chamber music and the Double Bass, and integrates different instrumental combinations of solo works, with emphasis on Brazilian popular music. The recital program is composed of arrangements that addresses the performance of instrument genres such as Milonga, the Chacarera and Chamamé, and other genres of Brazilian popular music like samba. The scientific article deals with the use of arrangements for chamber music with bass in popular Brazilian works. It presents alternatives for expanding the Brazilian popular chamber repertoire, through the discussion of expressive/technical resources applied to bass arrangements for various instrumental combinations. The main objective was to conduct a study on the use of arrangements for chamber groups with bass, demonstrating possibilities for increasing the repertoire and teaching materials. The methodological process was based on the literature review of the performance of the instrument in genres of popular music, particularly jazz, as well as chamber music and the main teaching methods used in the country. For that the use of technical resources from these two musical universes was discussed, applied in works of Brazilian popular music. The study sought to demonstrate that the use of arrangements of Brazilian popular music for chamber groups can serve as an alternative to expanding the repertoire and didactic material for teaching the instrument the bass.